Traumatic Brain Injury in Pregnancy - Santos, Letícia Adrielle dos; Pereira, Carlos Umberto; Paula, Maycon Cristian Gomes de; Kalkmann, Gabriela Ferreira; Rabelo, Nicollas Nunes (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2022)
Objective The present paper aims to provide a review on the main complications involving traumatic brain injury (TBI) during pregnancy and on the vegetative state after TBI.Methods A systematic review was performed in concordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) criteria checklist.Results Seven studies were included, of which four were case reports, one was a follow-up, one was a comparative study, and one was a literature review.Discussion Presence of neurological deficits such as hemiparesis, neonatal seizures, cerebral palsy, hemorrhage or hydrocephalus was observed in children of mothers who suffered trauma during pregnancy. The prolongation of a pregnancy in these victims, even in brain death, is within the reach of current medicine. Ethical issues must be considered when deciding to prolong a pregnancy of a woman in brain death.Conclusion For the evaluation of pregnant women with TBI, there is a protocol that can be followed in the emergency care service. The cases reported in the literature suggest that there is no clear limit to restrict support to a pregnant patient in a vegetative state. Further studies should be done to elucidate this matter.
Keywords: traumatic brain injury; pregnancy; management; developmental disabilities; persistent vegetative state